Individual differences in change blindness - Bergmann, Katharina (2016)
The present work shows the existence of systematic individual differences in change blindness. It can be concluded that the sensitivity for changes is a trait. That is, persons differ in their ability to detect changes, independent from the situation or the measurement method. Moreover, there are two explanations for individual differences in change blindness: a) capacity differences in visual selective attention that may be influenced by top-down activated attention helping to focus attention onto relevant stimuli b) differences in working memory capacity or in decision making. In accordance with this, age-related individual differences in the sensitivity for changes can be explained by attentional processes and by confidence in the own ratings. Together, the present work might form the basis for a more application-oriented research on individual differences in change blindness and its underlying processes.
Keywords: Hochschulschrift